Student academic help seeking in higher education: Navigating Bronfenbrenner’s systems. - McCutcheon, Sandi; Wood, Amanda; Bright, Miriam; Jilina, Polina; Walker, Alex (Journal of University Teaching and Learning Practice, 2025)
The academic success of students in higher education is influenced by a myriad of factors within and beyond the university context. These factors can challenge students, prompting them to seek academic help from teaching staff. It is important for teaching staff to be aware of the various factors impacting their students, so they can provide appropriate support and promote help-seeking behaviour in students. In recent years, academic help-seeking in higher education has gained significant research attention; yet the reasons for students seeking academic help have remained largely unexplored. Employing Bronfenbrenner’s ecological systems model as the theoretical framework, this article considers the personal and contextual factors that prompt students in higher education to seek academic support from teaching staff. Data was collected by purposeful random sampling through a survey, from university students studying in the faculty of humanities and social sciences at one university in Aotearoa, New Zealand. A deductive thematic analysis was undertaken. Findings showed that personal and multi-contextual factors can challenge students, prompting them to seek academic help; and have implications for teaching staff who work in higher education.